PENGEMBANGAN E-BOOK BERBASIS CANVA PADA MUATAN ILMU PENGETAHUAN ALAM MATERI SIKLUS AIR - Nida Nadia; Elly Sukmanasa; Lina Novita (STKIP Subang, 2025)
This study aims to (1) Develop teaching materials in the form of interesting and interactive E-Books on the content of science lessons for water cycle materials in grade V elementary schools, (2) Knowing the feasibility of Canva-based E-Books on the content of science lessons for water cycle materials in class V elementary schools. The rapid sophistication of technology requires teachers to use it in the learning process, one of which is to develop teaching materials. This research uses the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. In the limited trial stage, students' responses to the